2020
DOI: 10.1002/iub.2246
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the genetic polymorphisms of antioxidant enzymes on susceptibility to papillary thyroid carcinoma

Abstract: Several lines of evidences have indicated that inflammation play an important role in the carcinogenesis. During the inflammatory processes, free radical species are produced from oxidative stress. In normal conditions, enzymatic and nonenzymatic antioxidants remove these products. Manganese superoxide dismutase (MnSOD), glutathione peroxidase‐1 (GPx‐1), and catalase (CAT) are three important enzymes. Therefore, this study aimed to evaluate the effects of MnSOD (SOD2), GPX‐1, and CAT genetic polymorphisms on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Recent studies demonstrated that reduced expression of SOD2 increased the incidence of cancer, and it has been known that reduced expression levels of SOD2 might also result in increased DNA damage due to lower protection against ROS, and that the XPD mutant genotype had a lower capacity for repair than the wild type [23,30]. Consequently, these genotypes together can lead to an increase in cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that reduced expression of SOD2 increased the incidence of cancer, and it has been known that reduced expression levels of SOD2 might also result in increased DNA damage due to lower protection against ROS, and that the XPD mutant genotype had a lower capacity for repair than the wild type [23,30]. Consequently, these genotypes together can lead to an increase in cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…A protective effect of the Leu variant was found in the North Macedonia population, where the carriers of this variant allele had a lower risk of prostate cancer than wild-type individuals [88]. No associations were found between the rs1050450 polymorphism and other cancers, such as endometrial cancer in Polish women [71], papillary thyroid carcinoma in the Iran population [92], colorectal adenomas and colorectal cancer in Norwegian patients [64], and laryngeal cancer survival patients in the Poland population [83].…”
Section: Selenoproteins and Their Polymorphismsmentioning
confidence: 99%
“…There are several studies on the relationship between Catalase polymorphisms and the risk of various cancers [31], but there are very few studies on the correlation between the CAT-rs7943316 polymorphism and cancer risk. Several studies have proved that rs7943316 polymorphisms are unassociated with a risk of papillary thyroid carcinoma [32] or hepatocellular carcinoma risk [33]. Numerous researchers have submitted that Catalase polymorphisms may be linked with the possibility of many cancers such as cervical cancer, prostate cancer, pancreatic cancer, and colorectal cancer [7,[34][35][36].…”
Section: Distribution Of Cat (Rs7943316) Polymorphism Genotype With A...mentioning
confidence: 99%